Endoscopic port access resection of a massive atrial myxoma - van der Merwe, Johan; Casselman, Filip (SA Heart Journal, 2017)
We are witnessing an ongoing worldwide paradigm shift from conventional sternotomy access towards minimally invasive cardiac surgery (MICS). Endoscopic port access surgery (EPAS) is well established for the safe and durable resection of atrial myxoma (AM) and considered, by experienced surgeons to be a good MICS training platform once the initial EPAS learning curves are mastered. We report on the successful EPAS resection of an 8.5cm obstructive left AM in an 81-year-old patient, which is to our knowledge, the largest AM ever resected by robotic, or endoscopic, cardiac surgery. Post-operative recovery was uneventful and the patient was discharged home on the fi fth post-operative day. Clinical and echocardiographic follow-up at 12 months confi rmed an excellent functional recovery and the absence of residual or recurrent, tumour. This case aims to provide insights into the advantages and limitations of this approach.